(untitled) (LEGAL DIALOGICA, 2025)
The State Attorney (JPN) plays a crucial role as a representative of the state in civil and state administrative cases under Law Number 16 of 2004. However, the effectiveness of its role in the Gowa District Attorney’s Office remains limited, necessitating research as it relates to the recovery of state assets and the protection of the government’s legal interests. This study uses a qualitative approach with a normative legal framework, with data obtained through interviews with Gowa District Attorney officials and a review of literature and official documents. The results indicate that although the JPN has exercised its authority in accordance with procedures, both through litigation and non-litigation channels, the number of cases successfully decided is only three cases in the last five years, reflecting limited effectiveness due to low external understanding and limited internal resources. Abstrak Jaksa Pengacara Negara (JPN) berperan penting sebagai wakil negara dalam perkara perdata dan tata usaha negara berdasarkan Undang-Undang Nomor 16 Tahun 2004, namun efektivitas perannya di Kejaksaan Negeri Gowa masih terbatas sehingga perlu diteliti karena berkaitan dengan pemulihan aset negara dan perlindungan kepentingan hukum pemerintah. Penelitian ini menggunakan pendekatan kualitatif dengan kerangka hukum normatif, dengan data diperoleh melalui wawancara bersama pejabat Kejaksaan Negeri Gowa serta telaah literatur dan dokumen resmi. Hasil penelitian menunjukkan bahwa meskipun JPN telah melaksanakan kewenangannya sesuai prosedur, baik melalui jalur litigasi maupun non-litigasi, jumlah perkara yang berhasil diputus hanya tiga kasus dalam lima tahun terakhir, yang mencerminkan keterbatasan efektivitas akibat rendahnya pemahaman eksternal dan keterbatasan sumber daya internal. Kata Kunci ; Jaksa Pengacara Negara, Kejaksaan, Efektivitas, Perkara Perdata, Aset